AI: Unique Opportunities and Global Challenges – A Hybrid Approach to Modeling Reality and Its Perception - Mygal, Valeriy; Mygal, Galyna; Mygal, Stanislav (Qeios, 2024)
To solve the problems and challenges induced by digitalization and the use of specialized GenAI, a hybrid approach to modeling three-dimensional physical and digital reality is being developed. Based on a new philosophy of modeling, which includes second-order metascience, cybersemiotics, and cognitive metaphor, a structural-functional methodology for studying a hybrid environment is being developed, within which spatio-temporal connections of opposite phases of dynamic processes of various natures appear. It is shown that the synergy of the use of semiotics, cybersemiotics, and cognitive metaphor contributes to the formation of integrative metathinking and the choice of strategies for creative activity. At the same time, the development of the methodology itself (metathinking) through extreme principles, relationships, and structures, as well as the proposed hybrid universals, contributes to the formation of an individual’s learning cycle and style. The cognitive aspects of the manifestation of the phenomenon of the human factor in education and science, which limit the creative capabilities of the individual and give rise to systemic contradictions between physical and digital reality, are considered. In this case, obvious and hidden cognitive distortions arise, which give rise to new problems of safety (functional, informational, and physical), mental health, and diagnostics. Within the framework of the structural-integrative methodology, the foundations of an integrative meta-theory of natural structuring (transformation) of information flows (time series) of various natures into cognitive graphic images are created, which display the conjugate opposite phases of the functioning of the elements of complex dynamic systems, including the human body. To study transient functional states of a person and their quantitative assessment, original tools are proposed. They are based on the heuristic value of ancient signs – Ouroboros, Star of David, tetractys, Scandinavian runes, the use of which within the framework of a hybrid approach contributed to the study of parallels between the perception of physical reality and the mysticism of Eastern philosophy. In particular, the extreme principles of modern natural science have made it possible to establish a connection between the Star of David, the Merkabah (tree of life), and the Qabalah. Global challenges to mental health, safety, and professional activity are associated with the manifestation of cognitive and metacognitive distortions, which are induced by digitalization and depend on the psychophysiological state of a person (pilot, dispatcher, driver, etc.). They are studied by cognitive science and neuroscience, as well as ergonomics/human factors, engineering psychology, and human factors engineering. To reduce the risks of man-made disasters, the idea of complementarity of ergonomics, engineering psychology, and human factors engineering is being developed within the framework of metaergonomics of a hybrid environment. The cognitive metamodel of the metaergonomics structure takes into account the physical reality of consciousness and the virtual reality of the subconscious, the connection of which contributes to successful professional activity. New tools for modeling a neural network within the framework of natural computer science are proposed, which are based on the integrative metatheory of digital modeling of a hybrid subject environment. The new paradigm and principles of the natural knowledge base based on the structural-functional methodology and integrative meta-theory of modeling create unique opportunities for solving pressing problems through GenAI. The relevance and possibility of forming balanced creative-critical metathinking in the process of interaction in the digital world are discussed.